Membangun Peserta Didik yang Bermoral dan Berkarakter Pancasila, tanpa Bullying di SMP Darul Hikah Parongpong Kabupaten Bandung Barat - Hendrawan, Jajang; Halimah, Lili; Feniawati Darmana, Feniawati Darmana (Komunikasi, 2024)
Bullying is currently still a frightening thing in the world of education in Indonesia. Bullying is a behaviour that is not often encountered in everyday life, but bullying behaviour cannot be ignored. If left alone, it will seriously impact the social environment, especially at the stage of student development. Victims who are bullied are usually quiet children and children who have difficulty getting along with their friends. Bullying occurs due to several causal factors, namely, economic differences, religion, gender, traditions, and the habit of seniors to punish their juniors, which often occurs. There are feelings of revenge or jealousy, and there is a desire to dominate the victim with physical strength and sexual attraction. Apart from that, the perpetrator carries out bullying to increase his popularity among his fellow players (per group). Counselling activities at Darul Hikmah Parongpong Middle School, West Bandung Regency, were held in January 2024 and were attended by several class VII VIII students, teachers, and students who helped carry out community service. The activities carried out include counselling on the prevention and handling of bullying in the school environment using the seminar method. Hopefully, this outreach activity can provide students with an understanding that the impact will bring destruction to the souls of the younger generation.